DEVELOPING MULTIMEDIA-BASED ENGLISH LISTENING MATERIAL FOR ISLAMIC SENIOR HIGH SCHOOL - Yoki Irawan (Ta'dib, 2021)
This study aims at designing and developing multimedia-based English listening material for the first year students of an Islamic Senior High School. The study was a Research and Development (R&D) using ADDIE model. The respondents were 77 students and 4 English teachers of the first-year students of MAN 1 Kerinci. The data of this research were obtained through observation checklist, interviews, questionnaires, validation sheet, and checklist of the product practicality. The findings of product validation and try-out show that the product were interesting and easy to use with minor revisions. Further, it facilitates the students to have self-learning listening. The final product of the study is an executable file (* exe) attached on the CD. The result of the product validation, as well as the try-out, indicates that the material developed is categorized as "valid". The practicality of the material based on teachers and students’ responses indicates that the material developed is "practical" to (Nunan, 1999) use in the classroom.